Identification and functional characterization of a novel heterozygous missense variant in the LPL associated with recurrent hypertriglyceridemia‐induced acute pancreatitis in pregnancy. Issue 3 (21st January 2020) - Shi, Xiao‐Lei; Yang, Qi; Pu, Na; Li, Xiao‐Yao; Chen, Wei‐Wei; Zhou, Jing; Li, Gang; Tong, Zhi‐Hui; Férec, Claude; Cooper, David N.; Chen, Jian‐Min; Li, Wei‐Qin
Abstract: Background: Acute pancreatitis in pregnancy (APIP) is a life‐threatening disease for both mother and fetus. To date, only three patients with recurrent hypertriglyceridemia‐induced APIP (HTG‐APIP) have been reported to carry rare variants in the lipoprotein lipase ( LPL ) gene, which encodes the key enzyme responsible for triglyceride (TG) metabolism. Coincidently, all three patients harbored LPL variants on both alleles and presented with complete or severe LPL deficiency. Methods: The entire coding regions and splice junctions of LPL and four other TG metabolism genes ( APOC2, APOA5, GPIHBP1, and LMF1 ) were analyzed by Sanger sequencing in a Han Chinese patient who had experienced two episodes of HTG‐APIP. The impact of a novel LPL missense variant on LPL protein expression and activity was analyzed by transient expression in HEK293T cells. Results: A novel heterozygous LPL missense variant, p.His210Leu (c.629A > T), was identified in our patient. This variant did not affect protein synthesis but significantly impaired LPL secretion and completely abolished the enzymatic activity of the mutant protein. Conclusion: This report describes the first identification and functional characterization of a heterozygous variant in the LPL that predisposed to recurrent HTG‐APIP. Our findings confirm a major genetic contribution to the etiology of individual predisposition to HTG‐APIP. Abstract : The present study describes the first identification and functional characterization of a heterozygous variant in the LPL that predisposed to recurrent HTG‐APIP. Our findings not only underscore the importance of genetic defects in predisposing to HTG and/or acute pancreatitis but also shed new light on the complexity underlying the etiology of these phenotypes.